2021
DOI: 10.3390/met11091353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melt Overheating on Structure and Mechanical Properties of Al-Mg-Si Cast Alloy

Abstract: The paper discusses the complex effect of melt overheating with subsequent fast cooling down to the pouring temperature on the crystallization process, microstructure and mechanical properties of Al-Mg-Si aluminum alloy. The results obtained facilitated the establishment of rational modes of melt overheating, leading to a significant change in the dispersion and morphology of structural components. In particular, with an increase in the melt overheating temperature to 900 °C with holding and subsequent rapid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…b) Superaquecimento: trabalhos [9] onde a massa fundida foi superaquecida em 750, 800, 850 e 900°C, mostraram que os melhores parâmetros estruturais e morfológicos das ligas processadas foram alcançados na temperatura de superaquecimento de 900°C.…”
Section: Liga Al Cuunclassified
See 1 more Smart Citation
“…b) Superaquecimento: trabalhos [9] onde a massa fundida foi superaquecida em 750, 800, 850 e 900°C, mostraram que os melhores parâmetros estruturais e morfológicos das ligas processadas foram alcançados na temperatura de superaquecimento de 900°C.…”
Section: Liga Al Cuunclassified
“…Enquanto a taxa de resfriamento influenciou diretamente na forma regular da fase Al 2 Cu, alterando sua forma para dendrítica com o aumento da taxa de resfriamento. Discussões [9] diante do superaquecimento do fundido com resfriamento subsequente até a temperatura de vazamento da liga Al-Mg-Si, mostraram que houve uma mudança significativa na dispersão e morfologia dos componentes estruturais. Além do aumento significativo na microdureza de 38,21 para 56,5 HV da solução sólida de alumínio.…”
unclassified
“…The fast cooling is necessary to freeze superheated melt structure to pouring temperature. To the best knowledge of the authors, MTT has been studied on Al-20Si alloy 8,17 , Al-18Si alloy [21][22] , Al-15Si alloy 10,23 , Al-13Si alloy 24 and hypoeutectic alloys [25][26] and no study is conducted on the combined effect on MTT and Sr modifier on Al-14Si alloy. These previous studies have shown that individual MTT processes can reduce the size of primary Si, which leads to improvement in mechanical properties, especially ductility.…”
Section: Introductionmentioning
confidence: 99%
“…The production of AMCs was initially related to the method of powder metallurgy [7]. Modern technologies of aluminum matrix composites production mainly use the melt saturation with the use of powder materials [8,9]. In addition, special attention is currently paid to production of cast aluminum matrix composites by injecting finely dispersed high-melting additions directly in the process of casting (when pouring), which significantly increases the number of crystallization centers when the melt is cooled.…”
Section: Introductionmentioning
confidence: 99%